Development of control system for critical parameters of medical device sterization at an electron accelerator - Pomatsalyuk, R.I.; Shevchenko, V.A.; Shlyakhov, I.N.; Tenishev, A.Eh.; Uvarov, V.L. (Вопросы атомной науки и техники, 2015)
The hard- and software interfaces that provide on-line control and archiving of the basic parameters of the medical device sterilization (electron energy, beam current, width and shape of the beam scan, the conveyor speed and the absorbed dose in the treated products) have been developed at a radiation-industrial installation LU-10 of NSC KIPT. The main primary sensor of the control system is a stack-type monitor-absorber of the beam located behind the line of movement of the processed objects. Continuous monitoring of the processing parameters is performed by measuring and analyzing the currents from the plates of the monitor in a mode of "radiation shadow" created by irradiated objects. The structure of the control system, how it works and the calibration procedures for measuring channels are described.